The Improvement of Waste Cooking Oil Quality using H5-NZA Adsorbent in Fluid Fixed Bed Reactor - Donatus Setyawan P Handoko (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Investigation of waste cooking oil quality improvement have been done using H-zeolite as an adsorbent and fluid fixed bed reactor which was operated in a various temperatures. H-zeolite adsorbent was prepared through physical and chemical treatments as follows: washing, acid, calcination and oxidation. The characterization of this adsorbent covered cations contain (Pb, Cu, Zn, Na, K, Ca and Fe) using AAS, Si/Al ratio using AAS, surface area spesific, pore volume as well as pore diameter using surface area analyzer NOVA 1000, and acidity using gravimetric method with amonia adsorption. Quality parametric of cooking oil that were investigated covered water contain, acid as well as peroxide value and density. Sample of waste cooking oil was taken from cooking oil which have been previously used three times for frying kerupuk, tempe and tahu. Fifty milliliter waste cooking oil was flowed throught 10 g H-zeolite adsorbent in fluid fixed bed reactor which was operated at various temperatures (50, 70, 90, 110oC). The oil was placed in the bottle to be analyzed. The results showed that the adsorpstion process using H-zeolite adsorbent and fluid fixed bed reactor could reduce the water contain, acid and peroxide value and density, thus it improved quality of waste cooking oil. The optimum temperature was 70oC.